Familiar words can serve as a semantic seed for syntactic bootstrapping. Issue 1 (25th July 2020) - Babineau, Mireille; de Carvalho, Alex; Trueswell, John; Christophe, Anne
Abstract: Young children can exploit the syntactic context of a novel word to narrow down its probable meaning. But how do they learn which contexts are linked to which semantic features in the first place? We investigate if 3‐ to 4‐year‐old children ( n  = 60) can learn about a syntactic context from tracking its use with only a few familiar words. After watching a 5‐min training video in which a novel function word (i.e., 'ko') replaced either personal pronouns or articles, children were able to infer semantic properties for novel words co‐occurring with the newly learned function word (i.e., objects vs. actions). These findings implicate a mechanism by which a distributional analysis, associated with a small vocabulary of known words, could be sufficient to identify some properties associated with specific syntactic contexts. Abstract : Our study provides the first evidence that young children can rapidly track the distribution of a novel function word ('ko') and learn what type of semantic properties it can predict (novel action vs. novel object).